2009
DOI: 10.1161/hypertensionaha.109.132522
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Hypertension and Insulin Resistance in Subjects at Increased Cardiovascular Risk

Abstract: Abstract-Insulin resistance, a key component of the metabolic syndrome, is a risk factor for diabetes mellitus and cardiovascular disease. Acetyl-L-carnitine infusion acutely ameliorated insulin sensitivity in type 2 diabetics with insulin resistance. In this sequential off-on-off pilot study, we prospectively evaluated the effects of 24-week oral acetyl-L-carnitine (1 g twice daily) therapy on the glucose disposal rate (GDR), assessed by hyperinsulinemic euglycemic clamps, and components of the metabolic synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 46 publications
(47 reference statements)
2
73
1
2
Order By: Relevance
“…1 These findings led us to suggest that acetyl-L-carnitine treatment corrects a relative carnitine deficiency in this population. However, in a recent letter to the editor, Muniyappa 2 states that oral L-carnitine supplementation cannot achieve the plasma carnitine levels required to increase skeletal muscle carnitine concentration and improve insulin sensitivity.…”
Section: Oral Acetyl-l-carnitine Therapy and Insulin Resistancementioning
confidence: 96%
See 1 more Smart Citation
“…1 These findings led us to suggest that acetyl-L-carnitine treatment corrects a relative carnitine deficiency in this population. However, in a recent letter to the editor, Muniyappa 2 states that oral L-carnitine supplementation cannot achieve the plasma carnitine levels required to increase skeletal muscle carnitine concentration and improve insulin sensitivity.…”
Section: Oral Acetyl-l-carnitine Therapy and Insulin Resistancementioning
confidence: 96%
“…Moreover, 3 of 4 patients who regained normal glucose tolerance on acetyl-L-carnitine supplementation returned to their previous state of impaired glucose tolerance after acetyl-L-carnitine withdrawal. 1 As stated in our article, 1 we performed a pilot study aimed to explore the hypothesis that chronic acetyl-L-carnitine supplementation may have beneficial hemodynamic and metabolic effects in subjects at increased cardiovascular risk. The results confirmed the hypothesis and provided the background for a randomized, double-blind clinical trial, which we are currently running (identifier NCT00984750), to formally test the effects of acetyl-L-carnitine compared with placebo on blood pressure, lipid and metabolic profile, and kidney function in type 2 diabetes mellitus hypertensive patients.…”
mentioning
confidence: 99%
“…In a recent study, l-carnitine supplementation reduced tumor necrosis factor (TNF)-α, liver function parameters, plasma glucose levels and histological scores in NASH [121] . However, even if a majority of studies have shown that l-carnitine supplementation can improve factors associated with MetS and CVD [122][123][124][125] , recent evidences suggested that dietary l-carnitine may accelerate atherosclerosis via gut microbiota metabolites [126] .…”
Section: Other Anti-oxidant Drugsmentioning
confidence: 99%
“…Endothelial function, NO and oxidative defense are improved while oxidative stress and BP are reduced [144][145][146][147] . Human studies on the effects of L-carnitine and acetyl-L-carnitine are limited, with minimal to no change in BP [148][149][150][151][152][153] . In patients with MS, acetyl-L-carnitine at one gram bid over 8 wk, improved dysglycemia and reduced SBP by 7-9 mmHg, but diastolic BP was significantly decreased only in those with higher glucose [151] .…”
Section: Proteinmentioning
confidence: 99%
“…Human studies on the effects of L-carnitine and acetyl-L-carnitine are limited, with minimal to no change in BP [148][149][150][151][152][153] . In patients with MS, acetyl-L-carnitine at one gram bid over 8 wk, improved dysglycemia and reduced SBP by 7-9 mmHg, but diastolic BP was significantly decreased only in those with higher glucose [151] . Low carnitine levels are associated with a nondipping BP pattern in Type 2 DM [153] .…”
Section: Proteinmentioning
confidence: 99%